Third Five-Year Plan Andhra Pradesh Review of Progress 1965-66 - Planning Commission (Planning Commission, 1967)
The ceiling originally fixed for the Third Five-Year Plan of Andhra Pradesh was Rs. 505.00 crores. This was revised in 1963 to Rs. 312.66 crores in order to provide more funds for Minor Irrigation and Soil Conservation Programmes. The Central Assistance for this Plan was Rs. 203.06 crores, the balance Rs. 109.60 crores being the State’s share. The State Government represented to the Government of India in 1964 the need to provide additional assistance in Third Plan of Rs. 13.00 crores for Nagarjunasagar Project, Rs. 3.23 crores for Tungabhadra Project High Level Canal and Rs. 4.36 crores for Pochampad Project to get accelerated benefits of 5.79 lakh acres under Nagarjunasagar Project by June 1966.
Planning Department Hyderabad